Microbiological air quality in an urban solid waste selection plant (Italian Journal of Public Health, 2010)
Background: Exposure to bioaerosols may pose health risks to workers operating in the processing of UrbanSolid Waste (USW). The aim of this study is to evaluate microbiological air quality within an USW selectionfacility.Methods: Nine sampling points in an USW selection plant situated in central-southern Italy were selected.One outdoor sampling point provided the background data. Sampling was performed on a yearly basis (2005– 2009) upon request by the management of the selection plant. Total Mesophilic Counts (TMC), as well asfungal and Gram-negative concentrations were determined.Results: The highest viable fungal particles concentrations (medians) were found in waste delivery areas(about 20000 CFU/m3), while the lowest were found in the control rooms (485 – 967 CFU/m3). TMC (median)was highest (6116 CFU/m3) at the delivery pit, followed by the machine shop (3147 CFU/m3), where no wasteprocessing takes place. Medians of Gram-negative bacteria are below the suggested Occupational ExposureLimit of 1000 CFU/m3, although this limit was exceeded at several single time-points in the waste deliveryareas, and also in a personnel resting room. The lowest Gram-negative contamination was found in the controlrooms (medians
Keywords: waste selection; waste recycling; bioaerosol; air quality; micro-organisms